The Uncommon Localization of Herpes Zoster - Cukic, Vesna (Med Arch, 2016)
INTRODUCTION: Herpes zoster is an acute, cutaneous viral infection caused by the reactivation of varicella-zoster virus (VZV) that is the cause of varicella. It is an acute neurological disease which can often lead to serious postherpetic neuralgia (PHN). Different nerves can be included with the skin rash in the area of its enervation especially cranial nerves (CV) and intercostal nerves. CASE REPORT: In this report we present a patient with herpes zoster which involved ulnar nerve with skin rash in the region of ulnar innervations in women with no disease previously diagnosed. The failure of her immune system may be explained by great emotional stress and overwork she had been exposed to with neglecting proper nutrition in that period. CONCLUSION: Herpes zoster may involve any nerve with characteristic skin rash in the area of its innervations, and failure in immune system which leads reactivation of VZV may be caused by other factors besides the underlying illness.